Deep Geological Controls on Formation of the Highest‐Grade Uranium Deposits in the World: Magnetotelluric Imaging of Unconformity‐Related Systems From the Athabasca Basin, Canada - V. Tschirhart; E. G. Potter; J. W. Powell; E. A. Roots; J. A. Craven (Geophysical Research Letters)
Abstract Unconformity‐related uranium (URU) deposits in the Athabasca Basin, Canada, include the highest grade, large tonnage deposits in the world. Recent studies of the Patterson Lake corridor uranium deposits suggest a deep heat source enhances hydrothermal fluid flow and incursion of basinal brines along brittlely reactivated ductile shear zones. However, the spatial extent of the ore systems and lower crustal features capable of driving the hydrothermal cells remained largely unresolved. Three‐dimensional electrical conductivity models derived from inversion of magnetotelluric data and coincident gravity modeling identified a voluminous conductivity anomaly and corresponding gravity low related to a belt of high‐heat producing intrusions that dips below the deposit. Shallow conductive bodies are identified below the deposits and similarly prospective corridors. The volume and location of the intrusive bodies may have provided a source of radiogenic heat that helped drive remobilization of fluids along reactivated structures, redefining the spatial extent of URU systems.